Efeitos do metoprolol sobre as alterações histomorfológicas do coração produzidas pelo decanoato de nandrolona em ratos - Santos, Rosilene Aparecida Reis Rodrigues dos (2009)
The anabolic androgenic steroids (AAS) came from testosterone, with restricted use in medicine in some specific clinical conditions, and when correctly administrated are well tolerated. However, there is a potential risk to health the use of AAS without medical prescription and above the recommended dose, becoming evident the collateral effects. The risk of adverse cardiovascular effects increasing is a main concerning. The abusive use of anabolic androgenic steroids (AAS) is associated with left ventricular hypertrophy. The decanoate of nandrolone (nandrolone) is one of the most used AAS in the world. The regression of left ventricular hypertrophy is a point of interest because of the possible reduction of bad prognostic that it causes to the individual. Beta-blockers can revert the variations associated to ventricular remodeling and can show the progressive deterioration benefits from ventricular dysfunction. In this study was evaluated the effects of metoprolol on histomorphological profile of heart induced by AAS in rats. Four groups, each with 10 rats, were studied: 1) Control Group (C): rats that received twice a week injections of olive oil during five weeks as a control group (1 ml intramuscular);2) Nandrolone Group (N): rats that received twice a week injections of nandrolone during five weeks (15 mg/kg weight, intramuscular); 3) Metoprolol Group (M): rats that received twice a week injections of olive oil (1 ml intramuscular) during five weeks and daily injections of metoprolol (4 mg/kg weight, intraperitonial) during five weeks and 4) Nandrolone-Metoprolol Group (NM): rats that received twice a week injections of nandrolone (15 mg/kg weight, intramuscular) during five weeks and daily injections of metoprolol (4 mg/kg weight, intraperitonial) during five weeks. The animals were weighed to control body weight and heart beat frequency. The heart weight/animal weight ratio was quantified. The evaluation of ventricular remodelling was obtained through histological processing and morphological analyses, measuring miocytes diameter using HL Image 97. These microphotographies allowed the transversal diameter measurement of, at least, five ventricular fibers, with a total of 125 fibers measured by animal. The diameter of each fiber, in micrometers, was obtained in the HL Image 97 program. It was verified that the animals from Nandrolone (N) group showed a significant increasing of the ventricular fiber diameter compared with control group (C). In the association of nandrolone and metoprolol (NM) the diameter was 50 % lower than the group that received only nandrolone (N). The nandrolone decanoate promotes ventricular remodeling characterized by the increasing of myocardiocytes transversal diameter and the metoprolol associated with this nandrolone causes cardioprotective and repairing effect, decreasing the induced myocardium hypertrophy